Genotype-by-environment interaction in Corymbia citriodora (Hook.) KD Hill, & LAS Johnson progeny test in Luiz Antonio, Brazil - Souza, Bruno Marchetti de (2020)
Corymbia citriodora is one of the most cultivated hardwood species by small farmers in Brazil, and the most traded wood on the east coast of Australia due its high growth rate combined with high wood density. The study of genotype-by-environment interaction (GEI) is one of the most critical elements in the management of a breeding program to define breeding zones and to select genetic material targeted to specific environmental conditions. The aim of this research was to estimate genetic parameters in a C. citriodora progeny tests, established using 56 open-pollinated families in three sites with contrasting soil texture within the Luiz Antonio's experimental station, Brazil. The following traits were measured at 30 years of age: total height, diameter at breast height (DBH), stem form and survival. Based on this data, the individual volume was estimated. The harmonic mean relative performance of genetic values (MHPRVG) predicted by BLUP was used to evaluate productivity, stability and adaptability. The GEI was found to be not significant in all growth traits. A complex GEI was detected only for survival, supporting the importance of choosing the right genetic material of the species to specific sites. The present analysis showed a significant difference between families for DBH, survival and volume. In summary, the material studied presents potential to obtain attractive genetic gains through selection. However, in order to keep these sustained gains over the next selection cycles it is necessary to incorporate new genetic materials in order to increase genetic diversity.